Post-operative stereotactic radiosurgery following excision of brain metastases: A systematic review and meta-analysis. (January 2020) - Akanda, Zarique Z.; Hong, Wei; Nahavandi, Sofia; Haghighi, Neda; Phillips, Claire; Kok, David L.
Highlights: Following brain met excision, post-op radiosurgery (SRS) is increasingly being used. The efficacy and optimal delivery technique of SRS are topics of debate. Here we review all published cases of post-op SRS, totaling 3458 patients. The mean local control rate at 12 months was excellent (84%) with limited toxicity. 12 month local control was better with fractionated vs single-dose SRS (87% vs 80%, p  = 0.02). Abstract: Background: Following the resection of brain metastases, Stereotactic Radiosurgery (SRS) to the post-operative surgical cavity has increasingly replaced Whole Brain Radiotherapy (WBRT) as the standard of practice. There is however tremendous variation in the way SRS can be delivered and outcomes of SRS are yet to be systemically characterized. Methods: Pubmed, Medline, Embase, and Cochrane databases were searched through June 2019 to identify papers that examined post-operative SRS after resection of brain metastases. An aggregate data analysis was performed to estimate the pooled rate of local control at 12 months (LC12), radiation necrosis, and leptomengingeal disease dissemination as binary outcomes. We pre-specified a random effects model using the method of DerSimonian and Laird with the Mantel-Haenszel weighting scheme and a fixed continuity correction of 0.5. Heterogeneity was assessed using the I 2 statistic. Results: Fifty studies involving 3458 patients were included for analysis. LC12 across all studies was found to be 83.7%. Patients treated with fractionated SRS had better local control than patients treated with single fraction SRS (LC12 87.3% vs 80.0%, p  = 0.021) in a univariate analysis. There was no improved LC12 with the addition of a margin (LC12 of 84.3% vs 83.1% with no margin, p  = 0.71). Radiation necrosis was rare at 6.9% across all reported studies and leptomeningeal disease was found to be 13% across all reported studies. One year distant brain control was found to be 52.8%. Conclusion: Our review supports the use of post-operative SRS to the resection cavity as a safe and efficacious treatment option. Fractionated SRS appears to be beneficial and warrants further exploration.